THE EFFECT OF VARIATION IN COMPOSITION OF ALMOND, CORN, AND SOYBEAN ON THE CHARACTERISTICS OF COMPOSITE VEGETABLE MILK (ALCOSOY) - Asep Dedy Sutrisno (SEAN Institute, 2023)
This study aims to determine the effect of the composition of almond, corn, and soybean on composite vegetable milk (Alcosoy) and to determine the best almond, corn, and soybean ratio to produce the nutritional and sensory characteristics of composite vegetable milk (Alcosoy Milk). The experimental design of this research is using Completely Randomized Design (CRD) with four levels of ratio treatment almond, corn, and soybean, which are 1:1:1, 2:1:1, 1:2:1, dan 1:1:2. The treatment was repeated three times to obtain 12 experimental units. The obtained data analyzed by variance analysis, and the treatment affecting the observed parameters, the test continue with Duncan test. The result showed that the ratio of almond, corn, and soybean (Alcosoy) had a significant effect in content of protein, fat, fiber, total solids, calcium, potassium, Vitamin B1, β-carotene, and antioxidant activity as well as the hedonic test of taste and aroma, but insignificantly on the hedonic test of color and appearance of composite vegetable milk. The best almond, corn, and soybean milk obtained from 1:1:2 ratio with 3.9 % of protein content, 2:1:1 ratio with 3.51 % fat and 2.58 % fiber content, and 1:2:1 ratio with 12.38 % was the largest total dissolved solids, the Sensory test with response to color and appearance from normal to somewhat like for all compositions, while the most preferred response to taste and aroma is the composition 2:1:1.